Optimization pricing in the market for voluntary health insurance - KNEISLER, Olha; SHUPA, Lesia (Scientific journal «World of Finance», 2019)
Introduction. The modern market of voluntary health insurance is not able to cover a significant number of insurers. This means that insurance companies seek to attract a client among people at risk lower than the average, and, accordingly, reject the proposals for the insurance coverage of applicants with a risk level that is higher than the average.Purpose. In connection with the stated actual task the question arises the formation of scientifically-based insurance tariffs, which will ensure both the break-even activity of the insurance company, and the availability of insurance services for the largest possible population.Results. The question of the use of reasonable pricing in view of determining the correct and flexible cost of treatment and health rehabilitation, is a complex and important task for each insurer.Tariffs offered by insurers on the market should be calculated both from the actuarial and from the marketing point of view. Formation of optimal, scientifically substantiated and practically verified flexible pricing for voluntary medical insurance will improve the quality of medical care of the population, the creation of guarantees of reliable insurance protection and state interests.Conclusion. In order to optimize pricing a scientific and methodical approach to the formation of a flexible system of insurance tariffs with the use of the reliability theory of computational results modeled by Bülman-Straub is proposed. It is proved that the Bülman-Straub model, based on the determination of the confidence coefficient Z, allows us to assess the reliability of statistical information in the calculations and to determine the optimal amount of the insurance tariff for voluntary health insurance.